Open Coalition Law, Necessity or Threat? - Mądrzycki, Błażej (Acta Universitatis Lodziensis. Folia Iuridica, 2021)
From January 1, 2019. Amendments to the Act of July 5, 2018 amending the provisions on trade unions and some other acts apply (almost in full). Amendments to the Polish act are a consequence of the Committee for the Freedom of Association, Labor Law Organizations and the judgment of the Polish Constitutional Tribunal. The main and expected effect of the amendment is the extension of coalition freedom in trade unions. This issue is important not only for the consistency of the legal system with international law, but also for social reasons. Concluding civil law contracts in the place of employee forms of employment is a common practice in Polish conditions. The main problem is that the civil law contract has a purpose other than the employment contract. Contracts of mandate and provision of services are the basis for the implementation of actual and legal activities. Besides, the legislator does not have any real actions aimed at eliminating the defective practice. The text is an attempt to synthetically summarize the motives of the amendment, as well as its effects and tests.